Reconstructing democracy : grassroots Black politics in the deep South after the Civil War - Behrend, Justin, 1972- (The University of Georgia Press, 2015)
Former slaves, with no prior experience in electoral politics and with few economic resources or little significant social standing, created a sweeping political movement that transformed the South after the Civil War. Within a few short years after emancipation, not only were black men voting but they had elected thousands of ex-slaves to political offices. Historians have long noted the role of African American slaves in the fight for their emancipation and their many efforts to secure their freedom and citizenship, yet they have given surprisingly little attention to the system of governanc.